Soluble factors from Lactobacillus reuteri CRL1098 have anti-inflammatory effects in acute lung injury induced by lipopolysaccharide in mice - Griet, Milagros (2014)
We have previously demonstrated that Lactobacillus reuteri CRL1098 soluble factors were able to reduce TNF-a production by human peripheral blood mononuclear cells. The aims of this study were to determine whether L. reuteri CRL1098 soluble factors were able to modulate in vitro the inflammatory response triggered by LPS in murine macrophages, to gain insight into the molecular mechanisms involved in the immunoregulatory effect, and to evaluate in vivo its capacity to exert antiinflammatory actions in acute lung injury induced by LPS in mice. In vitro assays demonstrated that L. reuteri CRL1098 soluble factors significantly reduced the production of pro-inflammatory mediators (NO, COX-2, and Hsp70) and proinflammatory cytokines (TNF-a, and IL-6) caused by the stimulation of macrophages with LPS. NF-kB and PI3K inhibition by L. reuteri CRL1098 soluble factors contributed to these inhibitory effects. Inhibition of PI3K/Akt pathway and the diminished expression of CD14 could be involved in the immunoregulatory effect. In addition, our in vivo data proved that the PS induced secretion of the pro-inflammatory cytokines, inflammatory cells recruitment to the airways and inflammatory lung tissue damage were reduced in L. reuteri CRL1098 soluble factors treated mice, providing a new way to reduce excessive pulmonary inflammation.